Do gerenciamento de riscos à resiliência em cadeias de suprimentos - Martins de Sá, Marcelo (2017)
The water crisis is pointed out in global surveys carried out in last decade as a risk with high severity potential (WEF, 2007, 2016), considered the natural disaster that causes most deaths in all countries (BELOW; GROVER-KOPEC; DILLEY, 2007), and has a strong impact on food supply, resulting in damages for health, education, labor and economy of the affected regions. This thesis has found a unique opportunity to study the occurrence of a phenomenon with slow on-set characteristics, to explore the way in which it was perceived by managers, as well as the decisions that were considered for Risk and Resilience in Supply Chain Management. The main objective of this thesis was to investigate the development of supply chain resilience capabilities in a natural disaster context. To explore this context has the following research question: how do firms develop resilience supply chain capabilities when face a natural disaster? This thesis had a qualitative approach, through multiple case studies and the unit of analysis was the food and beverage supply chains (sugar cane and orange commodities). The results point to risk perception as responsible for the development of flexibility, collaboration, visibility and velocity capabilities. After risk perception, the respondents invested heavily in technologies to face the climate change phenomena to which they are exposed, evidencing the visibility capability on the event, mainly through sharing of useful information between the links of the supply chain members who faced the crisis. Another result indicates that velocity and collaboration are necessary in the response and recovery phases to achieve resilience. However, the present research showed that these capabilities are not present in all firms according to the cases studied. Both supply chains seek different paths to try to achieve the resilience necessary for normalization or improvement of their processes. It is concluded that the supply chains studied did not develop resilience to face future water crises in all links. The theoretical contributions of this thesis reside in three points: the first, the analysis of resilience capacities in the same study (as a “bundle of resources”), considering the context of the phases of a disruption with slow on-set characteristics. Second, studies with empirical evidence of the crisis environment or pre-rupture in supply chains that analyze in depth the response and recovery phases, especially for natural disasters with slow on-set, are rare. Third, the analysis of this phenomenon beyond dyads (suppliers-buyers) can be considered empiricaltheoretical contribution to supply chain discipline. From this knowledge, it is possible to adopt preparation strategies, such as increased flexibility and redundancy, investments in integrated communication systems between supply chain links to increase visibility and velocity of response, among other actions that involve the resilience capabilities studied. New agribusiness actions are needed to expand the existing agrienvironmental protocols, as well as new research, information sharing and debates, to maintain the adequate level of risk perception and focus on the recovery and conservation of relevant areas to improve water resources management.